Light Boxes : Leuchtenkastenkunst - Trescher, Stephan (Nürnberg : Verlag für moderne Kunst, 1999)
Abou-Chamat, Adidal ; Adams, Dennis ; Altenburger, Stefan ; Andessner, Irene ; Binder, Pat ; Blake, John ; Bonk, Ecke ; Braun, Gesine ; Brockmann, Elisabeth ; Byrne, David ; Dammbeck, Lutz ; Dauriac, Jacqueline ; Depman, Mark ; Detzner, Dieter ; Dott, Sergej Alexander ; Eckert, Karl-Heinz ; Flatz, Wolfgang ; Friedl, Peter ; General Idea ; Haneke, Egbert ; Haubitz, Sabine ; Hemmert, Hans ; Hershmann, Lynn ; Hirst, Damien ; Hoerler, Karin ; Hofstetter, Michael ; Horlitz, Andreas ; Jaar, Alfredo ; Katase, Kazuo ; Lafontaine, Marie-Jo ; Lewandowsky, Via ; Locher, Thomas ; Mori, Mariko ; Mullican, Matt ; Navares, Paloma ; Nicolai, Olaf ; Oehlert, Andreas ; Peeters, Sef ; Pflumm, Daniel ; Probst, Barbara ; Rauschenberg, Robert ; Raynaud, Patrick ; Rehm, Dieter ; Rinn, Rivka ; Sanguineti, Pietro ; Shalev-Gerz, Esther ; Shimizu, Yukara ; Staehle, Wolfgang ; Viktor & Rolf ; Wall, Jeff ; Walz, Rolf ; Zoche, Stefanie
Biografie
boek